2015
DOI: 10.1080/15427528.2014.980484
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Adapted and Exotic Drought-tolerant Maize Inbred Lines Under Full Irrigation and Rainfed Conditions in Nigeria

Abstract: Adoption of improved maize ( Zea mays L.) varieties in the rainforest agro-ecology of Nigeria largely depends on yielding potential and resistance to common foliar diseases. The present study aims at assessing the combining ability of a set of adapted and exotic drought-tolerant maize inbred lines under irrigated and rainfed conditions in Nigeria. Ninety-six hybrids generated using a North Carolina Design II scheme, and four checks were evaluated in a 10 × 10 triple lattice with three replications under full i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…This also suggests the need for selecting inbred lines at specific locations. However, mean squares of SCA x location interaction were non-significant for all investigated traits which were in agreement with the finding of Dagne, et al [39]; Adebayo and Menkir [31] and Fan, et al [36]. But, Tulu, et al [40] for grain yield and ear per plant, Noelle, et al [37] for days to 50% silking and ear aspect and Mosa, et al [41] for ear length, number of rows per ear and number of kernels per row found significant SCA x location interaction.…”
Section: Combining Ability Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…This also suggests the need for selecting inbred lines at specific locations. However, mean squares of SCA x location interaction were non-significant for all investigated traits which were in agreement with the finding of Dagne, et al [39]; Adebayo and Menkir [31] and Fan, et al [36]. But, Tulu, et al [40] for grain yield and ear per plant, Noelle, et al [37] for days to 50% silking and ear aspect and Mosa, et al [41] for ear length, number of rows per ear and number of kernels per row found significant SCA x location interaction.…”
Section: Combining Ability Analysissupporting
confidence: 91%
“…This indicates that variations among crosses through all the studied traits were mainly due to additive gene effect which was in accordance with the finding of Amare, et al [30]. Adebayo and Menkir [31];Satyanvesh [32];Tolera, et al [11] have earlier reported that additive gene actions were more important than non-additive gene actions for inheritance of grain yield and yield related traits. However, Aminu, et al [33] and Arsode, et al [34] reported that non-additive gene action was predominated in the inheritance of these traits.…”
Section: Combining Ability Analysissupporting
confidence: 89%
“…Maize (Zea mays L.) is one of the major cereal crops in sub-Saharan Africa (SSA). The contribution of maize to human calorific intake is 50%, 30% and 15% for southern, eastern, and West and Central Africa (WCA), respectively [1]. Normal endosperm maize, known to be lacking in provitamin A [2], tryptophan and lysine (PVATL) [3,4], is a major component of the food fed to babies (from two to three-month-old) and children of preschool age; this is usually done with no supplements in many developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, centers in Africa, such as the African Centre for Crop Improvement (ACCI) in South Africa and West Africa Centre for Crop Improvement (WACCI) in Ghana, with funding largely from the Alliance for a Green Revolution in Africa (AGRA) have contributed plant breeding capacity in Africa. Several of the breeders from ACCI and WACCI have identified germplasm that contain useful alleles for drought tolerance improvement of maize inbred lines and hybrids under drought stress ( Derera et al, 2008 ; Adebayo and Menkir, 2015 ; Meseka et al, 2018 ; Nasser et al, 2020 ). Evaluation of these germplasm has been achieved mainly through the utilization of conventional breeding via indirect selection using secondary traits drought selection indices.…”
Section: Plant Breeding Educationmentioning
confidence: 99%
“…Maize is the primary staple food for more than 900 million people globally and the third most important source of calories after rice and wheat ( Shiferaw et al, 2011 ; Adebayo and Menkir, 2015 ). With a decrease in rice production in China and India, and an increase in the demand for dairy and meat, global demand for maize is projected to double by 2050 ( Rosegrant et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%